Optimizing polycrystalline diamond compact bit selection and drilling parameters for deviated wells in the Majnoon Field, Iraq - Ahmed N. Al-Dujaili; Maaly S. Asad; Najah Saeed; Nurbol Tileuberdi (Scientific Reports)
Abstract Several mechanisms were postulated to reduce drilling problems, improve hole cleaning characteristics, and keep the bit in good condition for the second usage. This study was conducted on Majnoon Field in southeastern Iraq to optimize the bit and drilling parameters. The results indicated that the 16” SFD75D bit proved the preferred bit for both vertical and deviated wells due to its directional capabilities. MMD and MME were the best bit types for 12.25” and 8.5” sections and proved more successful than the FX and EQ types. The maximum weight on bit (WOB), Round per Minute (RPM), mud weight, and flow rate must be 25.45–73 klbs, 50-179.22, 10.5–10.8 ppg, and 662–940 gpm respectively, according to the drilling section. The wells with the J-shape showed a better penetration rate (increased 50–100%) and steadier torque than those with the S-shape for all drilling sections, with some deviations in the Shiranish, Sadi, and Tanuma Formations. The wells in the south have a sliding percentage of drilling hours more than in the north of the Field, and the inclination of the wells in the south was generally more stable and had lower hydraulics requirements than in the north of the Field.